Efficacy of xenogeneic fresh and lyophilized amniotic membranes on the healing of experimentally induced full-thickness skin wounds in dogs - Kamal H. Hussein; Esraa Motiea; Manal T. Hussein (Scientific Reports)
Abstract Wound healing is a complex process involving multiple phases aimed at repairing damaged tissues. Disruptions in this process can lead to chronic wounds and infections. Effective treatments that maintain cellular bioactivity while being cost-effective and easy to manufacture and store are needed. The amniotic membrane (AM) is highly biocompatible and rich in bioactive factors, making it valuable for regenerative medicine. Bovine AM is noteworthy for its large size, which facilitates its use in medical settings. However, preserving its bioactivity during storage is a challenge. Therefore, this study aimed to evaluate the effect of bovine lyophilized AM on full-thickness skin wound healing in dogs, compared to that of fresh AM. Bovine AM was collected, lyophilized, and characterized by quantifying growth factors, including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), as well as collagen, glycosaminoglycans (GAGs), elastin, and DNA. Additionally, the surface morphology was imaged using scanning electron microscopy (SEM). The effects of conditioned media from fresh and lyophilized AM on fibroblast and endothelial cell proliferation were compared. In vivo, three full-thickness skin wounds were created on the back in twelve dogs and treated with saline (control), fresh AM, or lyophilized AM, and monitored for healing over 1, 3, and 5 weeks. The fresh AM contained 57.3 ± 6.21 µg/mg collagen, 5.62 ± 1.1 µg/mg GAGs, 11.6 ± 4.52 µg/mg elastin, and 46.3 ± 12.8 ng/mg DNA, with VEGF and bFGF levels of 5.43 ± 2.485 and 1.97 ± 0.482 ng/mg, respectively. The lyophilized AM contained 217.74 ± 8.78 µg/mg collagen, 14.4 ± 1.56 µg/mg GAGs, 43.2 ± 6.8 µg/mg elastin, and 234.6 ± 21.5 ng/mg DNA, with VEGF and bFGF levels of 28.12 ± 7.6 and 13.3 ± 6.89 ng/mg, respectively. SEM revealed a monolayer with poorly defined borders in fresh AM, whereas lyophilized AM displayed a well-defined apical border with few microvilli. Lyophilized AM-conditioned media promoted greater endothelial cell and fibroblast proliferation. Compared with those in the fresh AM and control groups, wounds treated with lyophilized AM healed faster, with narrower edges and more pronounced re-epithelization and collagen remodeling at 1-, 3-, and 5-weeks post-wounding. Histopathology revealed quicker granulation and inflammatory cell infiltration in the first week for lyophilized AM, and better re-epithelization and collagen remodeling in subsequent stages. In conclusion, the amniotic membrane, particularly in its lyophilized form, offers significant benefits for skin wound healing due to its bioactivity, availability, and cost-effectiveness.